Influence of poly (Ethylene Glycol) on the characteristics of γ radiation-crosslinked poly (Vinyl Pyrrolidone)-low molecular weight chitosan network hydrogels - Maznah Mahmud,; Rusli Daik,; Zainah Adam, (Penerbit Universiti Kebangsaan Malaysia, 2018)
PEG at compositions of 10, 15 and 20 g were added into the initial formulation of hydrogel L, which was composed of 6 g low molecular weight chitosan (LMC) and 14 g poly (vinyl pyrrolidone) in 100 g of 2% lactic acid. The mixtures were moulded and exposed to γ radiation at 7 kGy. The hydrogels obtained were characterized in term of gel fraction, swelling property, syneresis effect, FTIR, XRD and cross section morphology. The results indicated PEG reduces almost 27% crosslinking density of the LMC-PVP hydrogel yet increased hydrogel’s water holding capacity from 450% and 480% to 750% and 650% in phosphate buffer solution (PBS) at pH5.5 and pH7.0, respectively. Also PEG enhanced the ability of LMC-PVP hydrogel to retain its moisture from dehydration at body temperature. The morphological study showed PEG developed thick pores wall and reduced the pores size of the hydrogels’ network.